Expressões marcárias e sustentabilidade no período pandêmico: um estudo sobre a identidade de marca da Osklen no Instagram - (:unkn) unknown (Universidade Federal do Pampa, 2024)
The purpose of this work is to bring reflections on sustainability in the fashion universe, with a specific focus on communication that takes place through digital platforms. Therefore, the objective of this research is to analyze Osklen's brand expressions on Instagram and their relationship with sustainability at the beginning of the 2020 coronavirus pandemic crisis. To compose basic knowledge regarding social responsibility, conscious consumption and sustainability in the fashion universe, we used the main concepts of Boff (2012), Zenone (2006), Ashley (2005) Samara and Morsch (2006), Carvalhal (2016) and Desirée (2019). The object of this study, presented as the clothing brand Osklen, through content published on Instagram @osklen, the brand's most relevant profile, is essential as a study agent for this work, being the main source of analysis. In this vein, we propose discussions and theoretical relationships, from authors who have already developed knowledge about recurring themes in research, such as the approaches of Costa (2011), Dias (2014), Perez (2016), Wheeler (2008) and Khauaja and Prado (2008) with perspectives on brand, brand image and identity; as well as understanding brands and habits during the pandemic period, based on Kotler (2021) and Alcoforado (2020). As a methodological path, we work with the perspective of bibliographic research by Gil (2008) and content analysis by Bardin (2016), with bibliographic support combined with methodology, it is possible to understand Osklen's trademark expressions through inferences and interpretations of posts published on its Instagram profile. As part of the results, taking into account the study corpus, the guiding concepts and the analysis method, it is possible to understand that Osklen has a strong alignment between its discourse and its sustainability practices. The brand frequently highlights topics such as environmental responsibility, ethics in the production of its products, use of certified raw materials, awareness and appreciation of all the impacts that the fashion sector causes on the environment.
Keywords: Moda; Sustentabilidade; Consumidores – Atitudes; Marca de produtos; Osklen; Instagram (Rede social on-line); Fashion; Sustainability; CNPQ::CIENCIAS SOCIAIS APLICADAS